Effect of Provideing Ergonomic Method Video to the Porters at Samarinda Pasar Pagi’s Dock - Rifani Amar Al Khairi; Iwan Muhamad Ramdan; Dina Lusiana Setyowati (Mulawarman International Conference on Tropical Public Health, 2025)
Background : According to the 2018 RISKESDAS data, the prevalence of musculoskeletal disorders in East Kalimantan was 8.12%, with the highest rates observed among farmers/laborers (9.9%), civil servants (7.5%), and fishermen (7.4%). Knowledge is one of the key factors influencing ergonomic posture. The use of interactive media, such as educational videos, can enhance the effectiveness of information delivery, thereby improving comprehension, knowledge, and attitudes toward ergonomic practices. Objective : Determine the effect of providing an ergonomic method video on the knowledge and work posture of porters at the Samarinda Pasar Pagi's Dock Research Methods/ Implementation Methods : This research is using quasi-experimental. Total of 30 respondents were involved as the research sample. Musculoskeletal complaints were measured using the Nordic Body Map instrument, while knowledgment & body posture was analyzed using questionnaire & Rapid Entire Body Assessment. Results : The experimental group showed a significant increase in knowledge (p = 0.003), indicating that the ergonomic lifting and carrying video effectively improved knowledge. However, there was no significant effect on reducing work posture risk on experimental group (p = 0.180). Conclusion/Lesson Learned : Based on the results and discussion, several conclusions can be drawn from the study : a. There was a significant increase in knowledge before and after the ergonomic lifting-and-carrying video intervention in the experimental group. b. There was no significant reduction in work posture risk in the experimental group after the intervention.